(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
Cybercrime is a crime that occurs in cyberspace which is different from criminal acts in general. In Indonesia, this is a new crime and requires special treatment. TheCybercrime Sub-Directorate of the North Sulawesi Regional Police Special Criminal Investigation is an agency that specializes in handling Cybercrime cases in the North Sulawesi region. The Professionalism factor is very important to be a benchmark for solving cybercrime cases in North Sulawesi handled by the cybercrime Sub Directorate of Special Criminal Investigation of North Sulawesi Regional Police. But seen from the settlement of cases in 2017 classified as still in the lower category. The purpose of this study was to determine the cause of the handling of cases conducted by Cybercrime Investigators in the Cybercrime Sub Directorate of Special Criminal Investigation Directorate of North Sulawesi Regional Police. This research uses a qualitative approach. Research informants were the Head of the Cybercrime Sub-Directorate, the Office of the Cybercrime Sub-Director, the Cybercrime Sub-Director and 4 members of the Cybercrime Sub-Director, which totaled 7 people. Data collection uses interview guidelines, while data analysis techniques use triangulation and data reduction techniques in terms of Well Motivation, Well Education, Well Trained, Well Equipment and Welfare. Based on the data analysis, it was concluded that the handling of cases conducted by Cybercrime Investigators in the Cybercrime Sub-Directorate of the North Sulawesi Regional Police Special Criminal Investigation Unit has not been carried out professionally because The professionalism of Cybercrime Investigators in the Cyber Criminal Investigation Directorate of North Sulawesi Regional Police is still lacking in terms of Well Motivation, Well Education and Well Equipment. Based on the results of the study, it can be recommended that the leadership of the Special Criminal Investigation Directorate can provide motivation by rewarding members who can resolve cases, the Leader can add personnel or members in the Special Criminal Investigation Cybercrime Sub Directorate who have an educational background related to Cybercrime Leadership can propose or propose an additional investigative budget in the Cyber Sub-Directorate. Keyword: Professionalism, Cybercrime, Investigator